Integrating Local Wisdom into ELT Materials for Secondary School Students in Semarang - Dwi Wulandari; Wiwiek Sundari; Cut Aja Puan Ellysafny (PAROLE: Journal of Linguistics and Education, 2020)
This study is Research & Development which contains three phases (explorative, model design, and try-out).  The research aims to develop a teaching material which integrates Javanese local wisdom   for the students of secondary school in Semarang.   Phase 1 (the explorative study) consists of two parts: book review and needs analysis (questionnaire and interview). The results of the first phase show that the existing  three books do not include aspects of  local wisdom. While the needs analysis show that the respondents  agreed to integrate aspects of local wisdom with the  benefits as follows: (a) supporting the learning process, (b) making the students understand  the materials  more easily, (c) enhancing the understanding of local cultures and character education. In phase 2 and phase 3 (model design and try-out in three schools), the findings indicate that  integrating local wisdom, i.e. a traditional song ”menthog-menthog” can enliven the classroom atmosphere. In addition, based on the respondent perception, the integration of local wisdom  would enrich the knowledge of local cultures as well as help the students understand ELT texts.